PRE-SERVICE TEACHER PERSPECTIVES ON MANAGING SPEAKING ANXIETY IN TEACHING EFL CLASSROOM (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Speaking anxiety is a significant challenge for pre-service teachers in English as a Foreign Language (EFL) classrooms. This study explores the causes of speaking anxiety as well as the coping management art utilized by pre-service teachers during their teaching practicum. Using a descriptive inquiry approach, data was collected from ten participants through an open-ended general inquiry. Findings indicated that the causes of anxiety included lack of confidence, fear of being wrong, student judgment, cultural disparities, and classroom management. To reduce anxiety, participants used cognitive, metacognitive, and social tactics, such as speech preparation, relaxation, peer support, and self-reflection. This research highlights the importance of integrating the management art of anxiety management into teacher education programs to improve teaching effectiveness as well as self-efficacy among future educators.